(untitled) (Communications in Computational Physics, 2020)
We extend classic Sommerfeld and Silver-Müller radiation conditions for bounded scatterers to acoustic and electromagnetic fields propagating over three isotropic homogeneous layers in three dimensions. If x=(x1,x2,x3)∈R3, with x3 denoting the direction orthogonal to the layers, standard conditions only hold for the outer layers in the region |x3|>‖x‖r, for γ∈(1/4,1/2) and x large. For |x3|